Modelling tumour-immunity interactions with different stimulation functions - Zhivkov, Petar; Waniewski, Jacek (Zielona Góra: Uniwersytet Zielonogórski)
Tumour immunotherapy is aimed at the stimulation of the otherwise inactive immune system to remove, or at least to restrict, the growth of the original tumour and its metastases. The tumour-immune system interactions involve the stimulation of the immune response by tumour antigens, but also the tumour induced death of lymphocytes.
Keywords: ordinary differential equations; critical points; stability analysis; immunotherapy